Should old-age benefits be earnings-tested? - Niku Määttänen; Panu Poutvaara (Institute for the Study of Labor (IZA), 2007)
We study the welfare effects of earnings testing flat-rate old-age benefits in a quantitative overlapping generations model with idiosyncratic labor income risk. In our model economy, even a moderate earnings testing reduces individuals' expected lifetime utility, whenever other taxes are taken into account. Moreover, it also lowers the realized lifetime utilities of those at the bottom of the lifetime utility distribution.
urn:nbn:de:101:1-2008042257
Keywords: 330; Soziale Sicherung; Alterssicherung; Lohn; Risiko; Wohlfahrtseffekt; Overlapping Generations; Wohlfahrtseffekt; Theorie